THE RELATIONSHIP BETWEEN THE DIGITALIZATION OF THE RADIOLOGY SERVICE SYSTEM AND THE PATIENT SATISFACTION LEVELS AT PKU MUHAMMADIYAH YOGYAKARTA HOSPITAL - Evrin Isna Nur Kuncara; Sulistyawati Sulistyawati; Rosyidah Rosyidah (HEARTY, 2026)
Digitalization in radiology services aims to enhance efficiency and facilitate easier access for patients. However, its implementation can elicit various responses from users. This study examines the relationship between the digitalization of radiology services and patient satisfaction levels. A quantitative analytic cross-sectional design was employed, involving 100 respondents selected incidentally from a population of 1,055 regular radiology patients. Data were analyzed using univariate and bivariate methods with the chi-square test at a 5% significance level. The results demonstrated a significant relationship between digitalization in terms of accessibility and patient satisfaction concerning product quality (p = 0.000) and service quality (p = 0.004). Meanwhile, digitalization related to efficiency showed no significant effect on satisfaction regarding product quality (p = 0.100), but was significantly associated with service quality (p = 0.040). These findings indicate that digitalization of radiology services has a significant impact on patient satisfaction, particularly through improved accessibility influencing both product and service quality, as well as efficiency affecting service quality. This underscores the importance of optimizing digital systems to improve the overall quality of healthcare services.